1992
DOI: 10.1037/0882-7974.7.1.138
|View full text |Cite
|
Sign up to set email alerts
|

Framing the construct of life satisfaction in terms of older adults' personal goals.

Abstract: Older adults' life satisfaction can be better understood in light of their personal goals. This study of 179 elders examined (a) how goals correlate with satisfaction, (b) whether elders maintain satisfaction by accommodating goals to past losses, and (c) how correlations between satisfaction and key predictors differ among groups with different goals. Satisfaction was related positively to social maintenance and energetic life-style goals and negatively to concerns for improvement, disengagement, stability, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
0
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 23 publications
3
54
0
4
Order By: Relevance
“…In earlier studies, the most common personal goals reported by older people have consistently been related to health, family and other close relationships, basic daily activities, independent living and leisure-time activities (Lapierre et al 1992(Lapierre et al -1993Lawton et al 2002;Saajanaho et al 2014a;Smith and Freund 2002). Among older people, higher age has been associated with fewer personal goals in total (Lawton et al 2002;Smith and Freund 2002) and less goal striving, especially in relation to leisure-time activities (Lawton et al 2002), an energetic lifestyle (Rapkin and Fischer 1992) and personal characteristics (Smith and Freund 2002). Spiritual goals (Lapierre et al 1992(Lapierre et al -1993Lawton et al 2002), health goals (Frazier et al 2002;Lapierre et al 1992Lapierre et al -1993Smith and Freund 2002) and goals related to independence and public services (Rapkin and Fischer 1992) have been reported to be more common among the oldest old.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…In earlier studies, the most common personal goals reported by older people have consistently been related to health, family and other close relationships, basic daily activities, independent living and leisure-time activities (Lapierre et al 1992(Lapierre et al -1993Lawton et al 2002;Saajanaho et al 2014a;Smith and Freund 2002). Among older people, higher age has been associated with fewer personal goals in total (Lawton et al 2002;Smith and Freund 2002) and less goal striving, especially in relation to leisure-time activities (Lawton et al 2002), an energetic lifestyle (Rapkin and Fischer 1992) and personal characteristics (Smith and Freund 2002). Spiritual goals (Lapierre et al 1992(Lapierre et al -1993Lawton et al 2002), health goals (Frazier et al 2002;Lapierre et al 1992Lapierre et al -1993Smith and Freund 2002) and goals related to independence and public services (Rapkin and Fischer 1992) have been reported to be more common among the oldest old.…”
Section: Introductionmentioning
confidence: 97%
“…These intentions, which describe motivational features behind people's actions, have been conceptualized as, for example, current concerns (Klinger 1975), personal strivings (Emmons 1986), possible selves (Markus and Nurius 1986), personal projects (Lawton et al 2002;Little 1983), and personal goals (Freund and Riediger 2006;Lapierre et al 1997;Rapkin and Fischer 1992). In the present study, we use the concept of personal goals, which has been defined as states that people strive to achieve or avoid in the future (Freund and Riediger 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations